2022
DOI: 10.4014/jmb.2110.10040
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria from Gamecock and Goat Originating from Phitsanulok, Thailand: Isolation, Identification, Technological Properties and Probiotic Potential

Abstract: From independent swab samples of the cloaca of indigenous gamecocks (CIG), anus of healthy baby goats (AHG), and vagina of goats (VG) originating from Phitsanulok, Thailand, a total of 263 isolates of lactic acid bacteria (LAB) were collected. Only three isolates, designated C707, G502, and V202, isolated from CIG, AHG, and VG, respectively, exhibited an excellent inhibitory zone diameter against foodborne pathogenic bacteria when evaluated by agar spot test. Isolates C707 and G502 were identified as Enterococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…monocytogenes , methicillin resistant S. aureus (MRSA), P. larvae , Vibrio alginolyticus , E. faecalis , B. cereus , and B. subtilis , were inhibited by 39, 37, 37, 16, 10, and 8 isolates, respectively. It is well known that LAB exhibit antibacterial activities against Gram-positive bacteria such as L. monocytogenes , S. aureus , E. faecalis , B. cereus , and B. subtilis [ 24 , 26 , 62 ]. Food was identified as the first source of infection of L. monocytogenes in humans, and today it is a public health concern related to septicemia, meningitis, gastroenteritis, pneumonia, and abortion [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…monocytogenes , methicillin resistant S. aureus (MRSA), P. larvae , Vibrio alginolyticus , E. faecalis , B. cereus , and B. subtilis , were inhibited by 39, 37, 37, 16, 10, and 8 isolates, respectively. It is well known that LAB exhibit antibacterial activities against Gram-positive bacteria such as L. monocytogenes , S. aureus , E. faecalis , B. cereus , and B. subtilis [ 24 , 26 , 62 ]. Food was identified as the first source of infection of L. monocytogenes in humans, and today it is a public health concern related to septicemia, meningitis, gastroenteritis, pneumonia, and abortion [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, all isolates were able to grow in 1% bile salts. These findings are not surprising, indeed several studies, with few exceptions, reported that LAB can survive under gastric conditions (low pH) and resist bile salts; moreover, these traits are particularly observed in LAB species of human and animal microbiota [27,33,62]. Another important criterion to be considered when selecting potential probiotic candidates is the strain surface hydrophobicity; indeed, high hydrophobicity of LAB strains correlate with their attachment to intestinal mucosal and epithelial cells [8].…”
Section: Safety Assessments and Probiotic Properties Of Bacteriogenic...mentioning
confidence: 88%